Involvement of prostaglandins in inflammation induced by latex of Calotropis procera - Vijay L. Kumar; Yatin M. Shivkar (Mediators of Inflammation, 2004)
INTRODUCTION: The aerial parts of the plant Calotropis procera produce milky white latex that causes inflammation of the skin and mucous membranes. Prostaglandins are one of the mediators released in an inflammatory response following induction of cyclooxygenase (COX). In the present study, we have evaluated the role of prostaglandins in inflammatory response elicited by the latex of C. procera.